Causes and reflexes of physical and psychological health in high school teachers - Pinheiro, Maria das Dores Carneiro; Torres, Caroline Maria de Oliveira; Almeida Neto, Honor de; Gedrat, Dóris (Acta Scientiarum. Health Sciences, 2024)
The psychological suffering of teachers is a relevant problem in the Brazilian society, being an emerging social demand since, in addition to influencing the professional’s mental and physical health, it affects their quality of life, as well as the performance at work. The research aimed to know the factors related to the physical and psychological health of high school teachers. This was a qualitative, exploratory, descriptive field study carried out in two high schools in the municipality of Santarém, state of Pará, Northern Brazil - one of which is public and the other private, with high school teachers as participants. The semi-structured script was used as a collection instrument. The results showed that factors causing damage to the professional physical and mental health are related to conflicts with students, lack of motivation to work, precarious environment, devaluation of the profession, long working hours, low wages, stress, frustration with the profession, depression, instability, among others. It was possible to identify the factors related to the process of physical and psychological illness in high school teachers, which contribute to healthproblemsanddifficultiestodeveloptheirprofessionalactivities. These are relevant results that can support actions and measures aimed at the well-being of teachers in their workplace.